OSTEOLOGY OF THE INDIAN MACKEREL, RASTRELLIGER KANAGURTA (CUVIER) - Gnanamuthu, J C (Indian Journal of Fisheries, 2011)
Rastrelliger kanagurta (the Indian Mackerel) is a fish of great commercialimportance and of wide geographical distribution in the Indo-Pacific region.The study of the biology of the mackerel has been receiving considerableattention in this region during recent years. One of the important aspectsof such work is the study on raciation. While the skeletal characters areof importance in such investigations, no standard description of the skeletalsystem of R. kanagurta or of any allied Indian species has been available sofar for reference. It was therefore necessary to undertake a detailed studyof the skeletal system of R. kanqgurta as a preliminary to studies on raciationin this species. The present paper deals with the osteology of the Indianmackerel.